AVALIAÇÃO DAS DIMENSOES DA GESTÃO DO CONHECIMENTO NO INSTITUTO FEDERAL FLUMINENSE. - Feres, Elisângela Monteiro (2014)
Knowledge has become an increasingly key feature that differentiates successful organizations in the market. For proper management of this knowledge could occurs, it is necessary to diagnose the situation in the organization, and from that diagnosis, develop action plans consistent with it. Thus, this study aims to assess the Knowledge Management in the Federal Institute of Education, Science and Technology Fluminense IFF. The main elements of the KM, as well as its importance in Brazilian public organizations were identified in the literature. To ascertain the existing conditions for implementing a KM program was used the method Organizational Knowledge Assessment (OKA), developed by the World Bank. This method was adopted by the Technical Committee for Knowledge Management and Strategic Information (TC-KMSI), of the Executive Committee of Electronic Government (ECEG), as a tool to be used by public federal organizations in the diagnostic the situation of the KM, providing subsidies for the development of a plan of KM. It is a comprehensive method that focuses on the Process, People and Technology, divided into 14 specific dimensions. In a comparative analysis, the results showed that the IF-Fluminense is below average compared to other Brazilian public institutions in almost all dimensions of the method. The analysis concluded that there is not a KM program in IF-Fluminense, but isolated KM initiatives, which affect a large number of dimensions of knowledge.